Analysis of Radiopaque Gastrointestinal Foreign Bodies Expelled by Spontaneous Passage in Children: A 15-Year Single-Center Study - Hung-Yu Yeh; Hsun-Chin Chao; Shih-Yen Chen; Chien-Chang Chen; Ming-Wei Lai (Frontiers Media S.A., 2018)
Background: Most ingested foreign bodies (FBs) pass spontaneously through the gastrointestinal (GI) tract, but only limited data on transit time are available. We evaluated the relationship of FB size and shape with transit time.Methods: We retrospectively reviewed medical records collected over 15 years (January 2001 to December 2015) on pediatric patients with radiopaque FBs in the GI tract. We categorized the FBs as regularly (round or spherical) or irregularly shaped (ovoid, long, flake-like, or projecting) and measured their sizes radiographically. The diameter of regularly shaped FBs and the length of irregularly shaped FBs were correlated with transit time.Results: In total, 484 patients with GI FBs were surveyed, and 267 (55.1%) FBs were radiopaque. Among the 267 radiopaque FBs, 88 (33.1%) required endoscopic removal and 7 (2.6%) underwent surgical intervention. Eighty-seven patients with single FBs in the GI tract for whom precise details of transit time were enrolled into the analysis of transit time; their mean age was 3.48 ± 2.21 years. Of the 87 FBs, 61 (70.1%) were regularly shaped, and 26 (29.9%) were irregularly shaped. The diameter of regularly shaped FBs was positively associated with transit time, as revealed by Mann-Whitney U test; diameters >1.5 and >2 cm were significantly correlated with longer transit times (both p = 0.003). A trend toward an increased transit time for long irregularly shaped FBs was also apparent; the p-values for lengths of 1.5, 2, and 2.5 cm were 0.824, 0.153, and 0.055, respectively. Under receiver operating characteristic (ROC) curve analysis, the optimal cutoff diameter for regularly shaped FBs, and length for irregularly shaped FBs, to predict a transit time of longer than 72 h were 1.95 and 2.25 cm, respectively.Conclusions: The passage rate of ingested radiopaque FBs is 64.4%. Small FBs that have passed the duodenal curve should be managed conservatively via clinical observation and radiographic surveillance. Our results indicate that the larger an FB is, the longer the transit time will be.